Gaya-Gaya Belajar Dalam Pembelajaran Mata Kuliah Bahasa Inggris di Program Studi Matematika Mahasiswa UKI Toraja (Jurnal Keguruan dan Ilmu Pendidikan, 2020)
The objective of this research was to identify the learning styles used by the second year students of Math Education Department of FKIP UKI Toraja.The reasercher employed a quantitative design. The population of this research were the students of Math Education Department of FKIP UKI Toraja in academic year 2018/2019. This research used random sampling technique which involved 30 students. The data of this research were collected through SAS questionnaire adapted from Rebecca L. Oxford (1993) to find out the students’ learning styles. The research result showed that the learning styles of the second year students of Math Education Department of FKIP UKI Toraja were visual 18 students (60%). They always prefer to learn with video or TV rather than with other media. They also feel more comfortable when the walls where they study or work have posters and pictures. They like to underline or highlight the important parts what they read and use color-coding to help them as they learn or work. They need written directions for tasks and have to look at people to understand what they say but get distracted by background noises. Auditory 7 students (23,33%), they always listen to music when they study or work and learn by listening to a lecture or a tape, rather than by reading. They also remember things better if they discuss them out loud, prefer to learn by listening to a lecture or a tape, rather than by reading and need oral directions for tasks. They can easily understand what people say even they can’t see them, can remember better what people say than what they look like and easily remember jokes what they hear and can identify people by their voices. Kinesthetic 5 students (16,66%), they always like a lot of physical activities, think better when they can move around and also enjoy building or making things and never get nervous when they sit still too long and need frequent breaks when they work or study and move their lips when they read silently.